Attitudes of Primary School Teachers towards Early Childhood Development in Zimbabwean Primary Schools - Mushoriwa, Taruvinga D; Muzembe, Hannah P (EDUCARE, 2011)
ABSTRACT: This study explored the attitudes of Zimbabwean primary school teachers towards the recently introduced Early Childhood Development (ECD) A and B classes, with the ultimate goal of assessing the acceptability, or otherwise, of the ECD. The survey research design was used to source data from 200 teachers comprising 100 infant and 100 junior teachers recruited from urban and rural primary schools. Overall, the study established that the majority of teachers (60%) in the study sample had a positive attitude towards the introduction of the ECD classes. There was no significant difference between rural and urban teachers but between infant and junior teachers. All in all, in the present writersâ view, the research outcomes from this study, indeed, hold promise for the ECD and tentatively provide mandate to the Zimbabwean government to go ahead with the idea of the ECD A and B classes. Based on these findings, the study strongly recommended that the Zimbabwean government should ensure that both human and material resources for the ECD classes are put in place urgently to capture, maintain, and increase the enthusiasm generated by its introduction.KEY WORDS: The attitudes, Zimbabwean primary school teachers, Early Childhood Development, and assessing the acceptability.Â About the Authors: Taruvinga D. Mushoriwa is a Lecturer at the Department of Educational Foundations and Management UNISWA (University of Swaziland), Private Bag 4 Kwaluseni, Swaziland M201, Southern Africa. Hannah P. Muzembe is a Lecturer at the Department of Educational Foundations UOZ (University of Zimbabwe), Harare, Zimbabwe, Africa. One of them can be reached at: tdmushoriwa@uniswacc.uniswa.szHow to cite this article? Mushoriwa, Taruvinga D. & Hannah P. Muzembe. (2011). âAttitudes of Primary School Teachers towards Early Childhood Development in Zimbabwean Primary Schoolsâ in EDUCARE: International Journal for Educational Studies, Vol.3(2) February, pp.117-128. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 17, 2010); Revised (January 17, 2011); and Published (February 17, 2011).